Managing forest ecosystems: the challenge of climate change - Bravo, Felipe. (Managing forest ecosystems, 2008)
With climate change now charging up the political agenda, there are three issues commonly making the headlines: carbon budgets, renewable energy, and the anticipated impacts of climate change. Equally important, though currently less well covered, is the issue how these effects might be mitigated. Given the significant role that forests play in the climate system – as sources, sinks, and through carbon trading – this book discusses the current scientific evidence on the relationships between climate, forest resources and forest management practices around the world. Drawing on expertise from forest scientists from several continents, the book presents both in depth analysis of the current knowledge, and a series of case studies which assess the biological and the economic impacts of climate change. It includes sections on forest responses to climate change, monitoring and modeling changes, economic and management implications, and carbon sequestration under specific management systems. The book will form a valuable resource for researchers and advanced students dealing with sustainable forestry, climate change issues and the effects of climate change on natural resource management. Overview of climate change and forest responses -- A mechanistic view of the capacity of forests to cope with climate change -- Greenhouse-gas emissions from temperate mountain forests -- Monitoring and modeling -- Estimating Carbon stocks and stock changes in forests: linking models and data across scales -- Forest eco-physiological models and carbon sequestration -- Influence of climatic variables on crown condition in pine forests of northern Spain -- economic and management impacts -- Influence of carbon sequestration in an optimal set of coppice rotations for eucalyptus plantations -- Use of forests and wood products to mitigate climate change -- Biomass forest in sweden and carbon emissions balance -- Taper equations and wood products: assessing the carbon flow of the forest through its products -- Forest management strategies and carbon sequestration -- Analysing the effects of forest structure on carbon stocks and timber production under changing management and climate -- Case studies -- Carbon sequestration in mediterranean pine forests -- Carbon sequestration of ponderosa pine plantations in northwestern Patagonia -- Assessing pine wilt disease risk under a climate change scenario in northwestern Spain -- Dynamics of soil carbon in primary and secondary tropical forests in colombia -- Carbon sequestration potential of mangroves in southeast asia -- Silviculture and carbon sequestration in mediterranean oak forests. variable riche en expressions et sentiment de votre pays d' origine.